Pengaruh Empati Terhadap Perilaku Prososial Pada Mahasiswa Perguruan Tinggi Islam - Lutfiyah; Fikrie; Muhamad Sabirin; Zulfa Jamalie (Jurnal Psikologi, 2025)
This study aims to examine the influence of empathy on prosocial behavior among students at Islamic Higher Education Institutions. Empathy is considered an important psychological component that can encourage individuals to show concern and help others voluntarily. This research employed a quantitative method with a correlational design. The population consisted of students at Islamic universities, and participants were selected using incidental sampling, resulting in a total of 60 respondents. Data were collected using an empathy scale and a prosocial behavior scale. The data were analyzed using simple linear regression. The results revealed that empathy has a significant influence on prosocial behavior among students in Islamic Higher Education Institutions